History as a Process of Formation and Comprehension of American IdentityReflections on Tigran Yepremian’s university textbook “History of the United States of America” - Hovhannisyan, Smbat; Stepanyan, Albert; Gasparyan, Karen (History and Culture, 2026)
The article examines Tigran Yepremian’s university textbook "History of the United States of America," analyzing it from both research and pedagogical perspectives. The authors present the fundamental methodological approaches of the textbook, emphasizing its interdisciplinary methodology, the study of American identity paradigms, the examination of crises as catalysts for development, and the analysis of state institutional functions. Besides these institutional issues, the textbook discusses the historical development of the principal elements of American national identity – science and technology, culture and religion, social psychology and civil liberties based on modern humanities. In this view, the problems of American elite groups, various social movements, and outstanding personalities are carefully interpreted in the textbook. The concern with the significant aspects of the history-teaching activity occupies a central position in Yepremian’s textbook. It aims to develop a critical approach for students to the process of American history and its principal lessons to be learned and modeled as the important issues of training in history and humanities. All the said highlight the significance of Yepremian’s textbook for students and the general public.